Comparison of plasma levels of nutrient-related biomarkers among Japanese populations in Tokyo, Japan, São Paulo, Brazil, and Hawaii, USA. Issue 2 (March 2015) - Iwasaki, Motoki; Franke, Adrian A.; Hamada, Gerson S.; Miyajima, Nelson T.; Sharma, Sangita; Ishihara, Junko; Takachi, Ribeka; Tsugane, Shoichiro; Le Marchand, Loïc
<x xml:space="preserve">Abstract</x> Previous studies of Japanese migrants have suggested that the increase in colorectal cancer rates occurring after migration is slower among Japanese Brazilians than among Japanese Americans. We hypothesized that this difference may partly reflect differences in vegetable and fruit intake between the populations. Using data from validation studies of food frequency questionnaires being used in comparative case–control studies of colorectal adenoma in Tokyo, São Paulo, and Hawaii, plasma carotenoid, retinol, tocopherol, and coenzyme Q10 levels were measured by high-performance liquid chromatography, and 25-hydroxy vitamin D levels were estimated by enzyme-linked immunosorbent assay. Plasma levels were compared by analysis of covariance between 142 Japanese in Tokyo, 79 Japanese Brazilians in São Paulo, and 78 Japanese Americans in Hawaii. Overall, we found significantly lower plasma carotenoid levels, except for lycopene levels, and retinol levels in Japanese Americans compared with Japanese in Tokyo and Japanese Brazilians. The plasma total carotenoid level was highest in Japanese Brazilians. Compared with the mean level among Japanese Brazilians (1741.2 ng/ml), P for difference was 0.03 among Japanese in Tokyo (1514.4 ng/ml) and less than 0.01 for Japanese Americans (1257.7 ng/ml). Plasma lycopene and tocopherol levels did not substantially differ between the three populations. We also found significantly lower plasma levels of 25-hydroxy vitamin D and total coenzyme Q10 in Japanese in Tokyo than in Japanese Americans and Japanese Brazilians. Higher levels of plasma carotenoids among Japanese Brazilians than among Japanese in Tokyo and Hawaii may have contributed to the slower pace of the increase in colorectal cancer rates observed in that population after migration.